Total quality management at logistics sector in Turkey - Kafadar, Saliha (My University, 2004)
Soyadı: Saliha KAFADAR letme netim ve Organizasyon Yrd. Doç.Dr. Varol Günyaşar Tez türü ve Tarihi: Yüksek Lisans - Aralık 2004 Lojistik Sektörü, Türkiye, Toplam Kalite, Müşteri Memnuniyeti

TÜRKİYEDE LOJİSTİK SEKTÖTÜNDE TOPLAM KALİTE YÖNETİMİ Dünya ticaretinin ana unsurlarından biri olan lojistik gelişmiş teknoloji ve uluslararası ticaret açısından gün geçtikçe önem kazanmaya başlamıştır.Seksenli, doksanlı yıllar arasında Turkiyede kara, hava ve deniz taşımacılığı olan lojistik sektörü doksanlı yılların ikinci yarısında teknolojik alt yapısını gelistirerek, dünya üzerindeki gelişmiş ülkelere ayak uydurmaya başlamıştır. Müşteri memnuniyeti ve bunun yaratılması, sürekliliği ve yüksek kaliteli servisin sürdürülebilirliği diğer ticari ve pazarlama aşamalarında olduğu gibi lojistik içinde önemli bir faktördür. Bununla birilikte kalite her kültür, her firma ve her çalışana göre görecelidir. Görünen odur ki, Türkiyede lojistik kelimesi bazı firmalar için kaliteyi artırma anlamına gelirken bazıları için kelimeden öteye geçmemiştir. Bununla birlikte ürün sınırlarını daraltıp serviste farklılık getirerek aynı ürün aynı pazara bir kaç firma tarafından sunulmaktadır. Bu koşullar altında en temel farklılık kalite, tecrübe, hız ve güleryüzlü hizmet ile sağlanır.Hazırlanan bu tezin amacı, herşeyden once, lojistiğin firma kültürü ile kalitenin kombinasyonu ve uygulaması konusunda bilgi vermesi içindir. Türkiyede lojistik sektörü açısından, sonuçlara bakılarak sektörün kalitesi nasıl artırılır konusu açıklanmış, firma açısından müşteri memnuniyetini geliştirmek için hangi servisler sunulmalı ve nasıl uygulanmalı hakkında sonuçlar bulunmuştur. Name and Surname: Saliha KAFADAR Field: Management Programme: Management and Organization Supervisor: Asst. Prof. Dr. Varol Günyaşar Degree Awarded and Date: Master - December 2004 Logistics Sector, Turkey, Total Quality, Customer Satisfaction ABSTRACT TOTAL QUALITY MANAGEMENT AT LOGISTICS SECTOR IN TURKEY The logistics which considered as one of the world's trades main components, in advanced technology and international trading capacities have commenced to become more valuable, as the time goes by. The advanced logistics sector which became an integrated of developed countries in the world, also in Turkey between eighties and nineties in the fields of the transportations of inland, in air, in rail-road and combined transportations, formed its infrastructure and commenced to progress in the second half of nineteen-ninety. The clients' satisfaction and its creation are very important factors at logistics like in any other trading and marketing progress, continuously and high in quality service must be ensured, as well. Although the concept of quality is variable, according to every culture, different firm establishment and the comprehension of each worker. Apparently, the progression at logistics sector in Turkey, has been announced, either some of the firms to increase the quality or the others only increase the number of interests to open up. In such a manner that, the logistics hadn't go through further than a name of a firm. However, by reducing the limits of product and service differentiation concept, the same product or service which has been submitted to the same market by several firms, so that the basic differentiation would be provided by quality, experience, speed and nice treatment. The purpose of this prepared thesis, before all else, gives us the understanding the logistics by combination of the firms' culture with quality and its application. Also, it is to announced the explanation of what should be done to improve the quality of sector according to the receipt results, to evaluate the satisfaction of clients from the angle of firm which provides services and how applied to them under the circumstances of the logistics sector of Turkey.
Keywords: Kargo hizmetleri; Lojistik; Taşımacılık (Yüzey taşımacılığı); Toplam Kalite Yönetimi